PENGARUH SECURITY, RELIABILITY, ASSURANCE DAN SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION PADA PLATFORM E-COMMERCE SHOPEE - Lestari, Rizki Amalia; Wuryan, Sophiyanto; Muniroh, Muniroh (Taksasila Edukasi Insani, 2025)
The rapid changes and transformation of digitalization experienced today, the quality of people’s lives is increasing rapidly, one of which is the development of e-commerce has changed consumer behavior that originally shopped offline now can easily be done online. This study aims to directly evaluate the influence of security, reliability, assurance, and service quality on customer satisfaction. This study uses a purposive sampling method involving 154 respondents who are active users of shopee e-commerce and have made purchases in the last 3 monts. Data were collected through an online survey and analyzed using the Statistical Package For The Social Sciences (SPSS). The results of the study indicate that security has a positive effect on customer satisfaction, reliability has a positive effect on customer satisfaction, assurance has a positive effect on customer satisfaction and service quality has a positive effect on customer satisfaction. This finding emphasizes that service quality plays an important role in shaping the shopping experience in increasing customer satisfaction. Practically, the shopee company focuses on improving these aspects in order to create a superior shopping experience in the long term for customers.Keywords: security, reliability, assurance, service quality, customer satisfaction.